Faktor – Faktor yang Mempengaruhi Kejadian Karies Gigi pada Anak Sekolah di SD Islamiyah Kecamatan Sekayu Tahun 2024 - Suzana, Amelia; Gustina, Erma; Rahutami, Syntia (Jurnal Akademika Baiturrahim Jambi, 2024)
Everyone is at risk of developing dental caries, but children are most at risk. The strategy to prevent dental caries is to reduce sugar consumption, which is the main public health approach that must be a priority. This study aims to determine the factors that influence the incidence of dental caries in school children at Islamiyah Elementary School, Sekayu District. The research was carried out at Sekayu Islamiyah Elementary School, Musi Banyuasin Regency from February to March 2024. The population of this research was students from Sekayu Islamiyah Elementary School in grades IV and V in 2024, namely 172 students. The sample consisted of 63 respondents. The sampling technique used was purposive sampling. Analysis of this research using the Pearson Chi-Square statistical test and Logistic Regression Test. Based on bivariate analysis using the chi-square test, there is no relationship between gender and dental caries (p-value 0.278), there is a relationship between knowledge and dental caries (p-value 0.022), there is a relationship between attitude and dental caries (p-value 0.012) , there is a relationship between toothbrush habits and dental caries (p-value 0.011), there is a relationship between diet and dental caries (p-value 0.013), and there is a relationship between the role of health workers and dental caries (p-value 0.024). It is hoped that elementary school teachers will monitor their students' consumption levels, because it cannot be denied that students will snack carelessly, especially sweet foods which have the potential to damage their teeth/cause dental caries..